Earliest Evidence of Preclinical Diabetic Retinopathy Revealed using Optical Coherence Tomography Angiography (OCTA) Perfused Capillary Density - Rosen, Richard B. (Am J Ophthalmol, 2019)
PURPOSE: To compare perfused capillary density (PCD) in diabetic patients and healthy controls using optical coherence tomography angiography (OCTA). METHODS: Forty controls, 36 diabetics without clinical retinopathy (NoDR), 38 with nonproliferative retinopathy (NPDR), and 38 with proliferative retinopathy (PDR) were imaged using SD-OCT. A 3×3 mm full-thickness parafoveal OCTA scan was obtained from each participant. Following manual delineation of the foveal avascular zone (FAZ), FAZ area, perimeter, and acircularity index were determined. Seven consecutive equidistant 200-µm-wide annular segments were drawn at increasing eccentricities from the FAZ margin. Annular PCD (%) was defined as perfused capillary area divided by the corresponding annulus area after subtraction of noncapillary blood vessel areas. Nonparametric Kruskal-Wallis testing with Bonferroni correction was performed in pairwise comparisons of group PCD values. RESULTS: The NoDR group demonstrated consistently higher PCD compared to the control group in all seven annuli, reaching statistical significance (36.6±3.30% vs 33.6±3.98%, P=0.034) at the innermost annulus (FAZ margin to 200-µm out). The NPDR and PDR groups demonstrated progressively decreasing PCD. Differences in FAZ metrics between the NoDR and control groups did not reach statistical significance. CONCLUSIONS: Relative to healthy controls, increased PCD values in the NoDR group likely represent an autoregulatory response to increased metabolic demand, while the decrease in PCD that follows in NPDR and PDR results largely from an incremental loss of capillary segments. These findings, consistent with previous studies, demonstrate the potential of OCTA as a clinical tool for earlier objective detection of preclinical diabetic retinopathy.